Different shades of green: how transnational actors frame nature as a solution to sustainability challenges in African cities - Rochell, Katharina; Bulkeley, Harriet; Runhaar, Hens (Local Environment, 2024)
Nature – based solutions (NBS) are increasingly being positioned within global discourses concerning how urban sustainability challenges can be addressed. To better understand to what extent, how, by whom and with what potential implications NBS are promoted in urban Africa, this paper focuses on transnational actors and presents a dataset covering 40 NBS initiatives in 57 cities across 19 African countries. A framing analysis is undertaken to understand to what degree NBS are mobilised in accordance with global discourses. To that end, the paper builds on existing work by Tozer et al. (2022, “Transnational Governance and the Urban Politics of Nature-Based Solutions for Climate Change.” Global Environmental Politics, 1–23) on globally circulating frames of urban nature. In further contributing to their framework, we delve into the underlying values or shades of green that are being signified through the frames by applying the IPBES Nature Futures Framework. Results indicate that urban nature comes to be seen as a solution within a climate resilience – integrated benefits nexus through which various types of transnational actors are bringing nature into the city. Two important findings can be highlighted: First, the deployed frames offer opportunities to address major African urban sustainability challenges, but initiatives may not yet be configured to adequately address their scope and magnitude. Second, the configurations of frames are predominantly informed by instrumental values that put "Nature for Society” perspectives in focus, missing opportunities for NBS to build on relational values, or “Nature as Culture” perspectives and for accommodating a plurality of worldviews on desirable futures for urban nature.